Informative value of neuropsychological tests for multiple sclerosis - A. R. Kabaeva; A. N. Boyko (Неврология, нейропсихиатрия, психосоматика, 2020)
Cognitive impairment (CI) occurs in 43–70% of patients with multiple sclerosis (MS) at both early and late stages of the disease. Cognitive deficit leads to disability regardless of the patient's physical condition and correlates with lower quality of life. A number of tests and batteries with good psychometric measures are used to assess the neuropsychological status of patients with MS. However, the validation and active clinical introduction of new or already existing neuropsychological tests remain relevant. Timely diagnosis of CI will be able to define the correct tactics of managing patients with MS and to monitor the efficiency of treatment.